2020
DOI: 10.3389/fphar.2020.00864
|View full text |Cite
|
Sign up to set email alerts
|

Phyllolobium chinense Fisch Flavonoids (PCFF) Suppresses the M1 Polarization of LPS-Stimulated RAW264.7 Macrophages by Inhibiting NF-κB/iNOS Signaling Pathway

Abstract: Background: M1 macrophage plays an important role in inflammatory reaction. In this study, potential anti-inflammatory effect of Phyllolobium chinense Fisch flavonoids (PCFF) was assessed via Zebrafish acute inflammation model in vivo and LPS-induced proinflammatory M1 macrophage model in vitro. Methods:The quality control of P. chinense Fisch flavonoids (PCFF) was analyzed by HPLC. Anti-inflammatory effect of PCFF on the acute injured zebrafish was evaluated by the migration of fluorescence labeled macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Therefore, reductions in NO level as observed in our results suggest that flavonoids fractions nullified the production of NO by inhibiting the expression of iNOS [54]. Fan et al [55] showed that flavonoids derived from Phyllolobium chinense produced similar NO-lowering effect by specific inhibition of iNOS in Zebrafish model. Malondialdehyde (MDA), an index of oxidative damage to lipids [13], increased dramatically in the plasma, liver and the kidneys of the arsenic exposed group (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, reductions in NO level as observed in our results suggest that flavonoids fractions nullified the production of NO by inhibiting the expression of iNOS [54]. Fan et al [55] showed that flavonoids derived from Phyllolobium chinense produced similar NO-lowering effect by specific inhibition of iNOS in Zebrafish model. Malondialdehyde (MDA), an index of oxidative damage to lipids [13], increased dramatically in the plasma, liver and the kidneys of the arsenic exposed group (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…The results of immunocytochemistry suggested that MBVP cells were PDGFRβ + cells and could be used as the PDGFRβ + pericytes model in vitro (Figure 3A). In addition, we induced and identified M1 or M2 polarization of macrophages according to previous reports (Kigerl et al, 2009;Hiroi et al, 2013;Fan et al, 2020). The results of Western blot showed that compared with other groups, M1 macrophages significantly expressed iNOS while M2 macrophages significantly expressed CD206 (p < 0.0001 for iNOS, p < 0.001 for CD206, Figures 3B-D).…”
Section: Identification Of Pdgfrβ + Pericytes and Macrophages Polarization In Vitromentioning
confidence: 89%
“…Here, we investigated whether also macrophage cell population might be targeted by A. tonkinensis decoction and by its major component TAT-2, assessing if they could interfere in macrophage acquisition of a pro-inflammatory phenotype, and decrease formation of osteoclasts, key cells in the RA pathologic joint damage. Using the established inflammation in vitro model of RAW264.7 macrophage cell line conditioned with LPS (Fan et al, 2020), we investigated the effects on nitric oxide (NO) and IL-6 production. Moreover, inducing osteoclastogenesis in RAW264.7 by RANKL protein (Kim et al, 2019), we evaluated the inhibition of osteoclast differentiation process and the decrease of its markers, also exploring the interference at RANK signaling level.…”
Section: Introductionmentioning
confidence: 99%